Deep-Sea DC Resistivity and Self-Potential Monitoring System for Environmental Evaluation With Hydrothermal Deposit Mining - Kasaya, Takafumi; Iwamoto, Hisanori; Kawada, Yoshifumi (Frontiers in Earth Science, 2021)
Environmental impact assessment has become an important issue for deep-sea resource mining. The International Seabed Authority has recently developed recommendations for guidelines on environmental assessment of resource mining effects. Several research and development groups have been organized to develop methods for environmental assessment of the seafloor and sub-seafloor under the “Zipangu in the Ocean program”, a part of the Cross-ministerial Strategic Innovation Promotion Program managed by the Cabinet Office of the Japanese government. One attempt planned for long-term environment and sub-seafloor structure monitoring uses a cabled observatory system. To support this observatory plan, we began development of a system to monitor the sub-seafloor resistivity and self-potential reflecting the physicochemical properties of ore deposits and the existence of hydrothermal fluid. The system, which mainly comprises an electro-magnetometer and an electrical transmitter, detects spatio-temporal changes in subseafloor resistivity and in self-potential. Because of the project’s policy changes, cabled observatory system development was canceled. Therefore, we tried to conduct an experimental observation using only a current transmitter and a voltmeter unit. Data obtained during three and a half months show only slight overall apparent resistivity variation: as small as 0.005 ohm-m peak-to-peak. The electrode pair closest to the hydrothermal mound shows exceptionally large electric field variation, with a semidiurnal period related to tidal variation. Results indicate difficulty of explaining electric field variation by seawater mass migration around the hydrothermal mound. One possibility is the streaming potential, i.e., fluid flow below the seafloor, in response to tides. However, we have not been able to perform rigorous quantitative analysis, and further investigation is required to examine whether this mechanism is effective. The system we have developed has proven to be capable of stable data acquisition, which will allow for long-term monitoring including industrial applications.